Mechanism of Inhibitory Action on Platelet Activation of a Phospholipase A2 Isolated from Lachesis muta (Bushmaster) Snake Venom - Fuly, André L; Machado, Olga L T; Alves, Elias W; Carlinis, Célia R (Thrombosis and Haemostasis, 1997)
Crude venom from Lachesis muta exhibited procoagulant, proteolytic and phospholipase A2 activities. A phospholipase A2, denoted LM-PLA2 was purified from L. muta venom to homogeneity, through a combination of chromatographic steps involving gel-filtration on Sephacryl S-200 HR and reverse phase chromatography on a C2/C18 column. LM-PLA2 presented a single polypeptide chain with an isoelectric point at pH 4.7 and apparent molecular weight of 17 kDa. Partial aminoacid sequence indicated a high degree of homology for LM-PLA2 with other PLA2 from different sources.LM-PLA2 displayed a potent enzymatic activity as measured by indirect hemolysis of red blood cells but it was neither lethal when injected i.p. into mice nor did it present anticoagulant activity. Furthermore, LM-PLA2 displayed a moderate inhibitory activity on the aggregation of rabbit platelets induced by low levels of ADP, thrombin and arachidonate. In contrast, platelet aggregation induced by high doses of collagen was strongly inhibited by LM-PLA2 as well as ATP-release. Treatment of the protein with p-bromophenacyl bromide or 2-mercapto-ethanol, as well as thermal inactivation studies, suggested that the platelet inhibitory effect of LM-PLA2 is dependent on its enzymatic activity. Thus, the platelet inhibitory activity of LM-PLA2 was shown to be dependent on the hydrolysis of plasma phospholipids and/or lipoproteins, most probably those rich in phosphatidylcholine. Surprisingly, lyso-phosphatidylcholine released by LM-PLA2 from plasma was shown to preferentially inhibited collagen-induced platelet aggregation, in contrast to other PLA2s, whose plasma hydrolytic products indistinctly affect platelet’s response to several agonists.